Corrective osteotomy is an effective method of treating distal radius malunions with good long-term functional results. Issue 3 (March 2017) - Mulders, M.A.M.; d'Ailly, P.N.; Cleffken, B.I.; Schep, N.W.L.
Abstract: Introduction: Malunion occurs in approximately 23% of non-operatively treated and 11% of operatively treated distal radius fractures. The decision whether to correct a malunion is primarily based on functional impairment and wrist pain. The purpose of this study was to assess the long-term functional outcomes of corrective osteotomies for symptomatic malunited distal radius fractures. Methods: All consecutive corrective osteotomies of the distal radius performed in one centre between January 2009 and January 2016 were included. The primary outcome was the functional outcome assessed with the Disability of the Arm, Shoulder and Hand (DASH) and the Patient-Rated Wrist Evaluation (PRWE) score. Secondary outcomes were range of motion, grip strength, pain as indicated on the Visual Analogue Scale (VAS) before and after corrective osteotomy, radiological parameters, time to union and complications. Additionally, we aimed to determine if there were any difference in graft versus no graft usage. Results: A total of 48 patients were included. The median age was 54.5 years (IQR 39–66) and 71% was female. The median time to follow-up was 27 months. The median DASH and PRWE score were respectively 10.0 (IQR 5.8–23.3) and 18.5. (6.5–37.0). Except for pronation and supination, range of motion and grip strength of the injured wrist were significantly less compared to the uninjured side. Palmar and dorsal flexion and radial and ulnar deviation of the injured wrist were significantly less compared with the uninjured side. VAS pain scores decreased significantly from 6.5 preoperative to 1.0 postoperative. The median time to union was 23 weeks (IQR 12–29.5). Eighteen patients (38%) had a complication for which additional treatment was required. Except for a significant difference in radial inclination and length after the corrective osteotomy in favour of graft usage, there were no significant differences between graft an no graft usage. Conclusions: Corrective osteotomy is an effective method of treating symptomatic distal radius malunions with good long-term functional results, measured with the DASH and PRWE score, and improvement in radiographic parameters and pain scores. Additionally, no differences in functional outcomes were found between graft and no graft usage.